Minimal clinically important differences in the Edmonton Symptom Assessment Scale in cancer patients: A prospective, multicenter study. Issue 17 (8th June 2015) - Hui, David; Shamieh, Omar; Paiva, Carlos Eduardo; Perez‐Cruz, Pedro Emilio; Kwon, Jung Hye; Muckaden, Mary Ann; Park, Minjeong; Yennu, Sriram; Kang, Jung Hun; Bruera, Eduardo
Abstract : BACKGROUND: The Edmonton Symptom Assessment Scale (ESAS) is widely used for symptom assessment in clinical and research settings. A sensitivity‐specificity approach was used to identify the minimal clinically important difference (MCID) for improvement and deterioration for each of the 10 ESAS symptoms. METHODS: This multicenter, prospective, longitudinal study enrolled patients with advanced cancer. ESAS was measured at the first clinic visit and at a second visit 3 weeks later. For each symptom, the Patient's Global Impression ("better, " "about the same, " or "worse") was assessed at the second visit as the external criterion, and the MCID was determined on the basis of the optimal cutoff in the receiver operating characteristic (ROC) curve. A sensitivity analysis was conducted through the estimation of MCIDs with other approaches. RESULTS: For the 796 participants, the median duration between the 2 study visits was 21 days (interquartile range, 18‐28 days). The area under the ROC curve varied from 0.70 to 0.87, and this suggested good responsiveness. For all 10 symptoms, the optimal cutoff was ≥1 point for improvement and ≤–1 point for deterioration, with sensitivities of 59% to 85% and specificities of 69% to 85%. With other approaches, the MCIDs varied from 0.8 to 2.2 for improvement and from −0.8 to −2.3 for deterioration in the within‐patient analysis, from 1.2 to 1.6 with the one‐half standard deviation approach, and from 1.3 to 1.7 with the standard error of measurement approach. CONCLUSIONS: ESAS was responsive to change. The optimal cutoffs were ≥1 point for improvement and ≤–1 point for deterioration for each of the 10 symptoms. Our findings have implications for sample size calculations and response determination. Cancer 2015;121:3027–3035. © 2015 American Cancer Society . Abstract : When a symptom response is being assessed, how much of a change on a 0‐ to 10‐point numeric rating scale is considered clinically significant? In this multicenter, prospective, longitudinal study involving 796 patients with advanced cancer, the minimal clinically important difference is universally a 1‐point difference for both improvement and deterioration for each of the 10 symptoms in the Edmonton Symptom Assessment Scale, one of the most widely used symptom assessment batteries in oncology.